(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The effects of aluminum and copper additives (0, 2, 4 and 6 wt. %) are investigated on graphite morphology, microstructure and compressive behavior of ductile iron specimens manufactured by sand casting technique. The graphite morphology and microstructure are evaluated using optical microscopy (OM) and scanning electron microscopy (SEM) equipped image processing software. To study the mechanical properties, the compression test is conducted on the specimens. The results indicate that the surface fraction and nodule count of graphite decrease by increasing the amount of aluminum from 0 to 2 wt. % and then, increasing from 2 to 6 wt. %. In addition, the nodularity of graphite increases by increasing the amount of aluminum. By increasing the amount of copper, the surface fraction and nodule count of graphite increase and nodularity of graphite decreases. The addition of aluminum and copper decreases the surface fraction of ferrite and increases the surface fraction of pearlite in the microstructure. By increasing the amounts of aluminum and copper, compressive stress vs. strain curves are shifted upwards, and modulus of elasticity, yield strength, maximum compressive stress and fracture strain increase. In compare with copper, aluminum has a greater influence on the mechanical properties of the ductile iron.